Biada zwyciężonym – gospodarka i relacje społeczne w kulturze lateńskiej - Gralak, Tomasz (Folia Praehistorica Posnaniensia, 2021)
The economy of any community depends on the values which are considered to be the most important. Social organization and technologies are subordinated to their implementation. In traditional societies, including people of the La Tène culture, the most significant issues concerned the status of individuals and the resulting interpersonal relations. The position in rank was manifested and gained through participation in military expeditions. The economy was subordinated to military action. Nonetheless, new technologies and financial solutions created opportunities for military success. This, however, has its price in enormous social inequalities and almost permanent war.